Longitudinal study of cross-reactive antigenemia in individuals with high Loa loa microfilarial density reveals promising biomarkers for distinguishing lymphatic filariasis from loiasis - Djune-Yemeli, Linda; Hertz, Marla; Nana-Djeunga, Hugues C.; Rush, Amy; Erdmann-Gilmore, Petra; Sprung, Robert; Bopda, Jean Gabin; Townsend, Reid; Netongo, Palmer Masumbe; Kamgno, Joseph; Budge, Philip J. (Frontiers in Parasitology, 2023)
Background and Methods: Circulating Loa loa antigens that cross-react with target antigensare often detected in individuals with heavy L. loa infections by in diagnostic tests for lymphatic filariasis (LF) caused by Wuchereria bancrofti are often detected in individuals with heavy L. loa infections. This is a major challenge to LF mapping and elimination efforts in loiasis co-endemic areas. However, it also provides an opportunity to identify antigen biomarkers for loiasis. To determine which L. loa antigens might be promising biomarkers for distinguishing true LF from loiasis, we screened for L. loa antigens in a group of individuals with heavy L. loa infections living in the Okola Health District of Cameroon. In this longitudinal study, participants were tested for cross-reactive antigenemia by filariasis test strip (FTS), ELISA, and western blot, and were monitored for FTS status at 6, 9, 12, and 15 months post-enrollment. We then identified specific circulating L. loa antigens by liquid chromatography-tandem mass spectrometry (LC-MS/MS) from baseline and 15-month plasma samples.Principal Findings and conclusions: Among 73 FTS-positive (FTS+) and 13 FTS-negative (FTS-) participants with high L. loa microfilarial loads, 82.883% maintained their FTS status over the course of the study, while 17.2% experienced at least one FTS conversion event (from FTS+ to FTS-or vice versa). Cross-reactive antigens were detected in both FTS+ and FTS-sera by western blot, and there was poor agreement in antigen detection by FTS, western blot, and ELISA methods. One protein family, a group of NASNas-14 metalloproteases, was detected by LC MS/MS in >80% of tested samples, including FTS-samples. These data identify NASNas-14 as a promising loiasis biomarker potentially capable of distinguishing loiasis from lymphatic filariasis.